Masivní ruptura rotátorové manžety - srovnání mini-open a artroskopické rekonstrukce. Část 2 / Artroskopická rekonstrukce - Musil, David; Sadovský, Pavel (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2007)
PURPOSE OF THE STUDY In this study the results of arthroscopic repair of massive rotator cuff tears are evaluated and compared with those of mini-open surgery published in Part 1. MATERIAL By the year 2006, of 176 patients undergoing the reconstruction of massive rotator cuff tears in our department, 77 were treated by arthroscopy. In this group there were 50 men; the dominant arm was operated on more frequently (60x). The average age of the patients was 55 years (range, 37-74). METHODS Surgery is carried out under combination of general anesthesia and an interscalene brachial plexus block, in a lateral recumbent position, with traction applied to the axis of the limb abducted at 40 degrees. Standard arthroscopic portals are used. After exploration of the glenohumeral Joint and thorough bursectomy, the torn rotator cuff tendons are mobilized and an insertion site is prepared. Using Spiralok (Mitek) anchors loaded with two Strands of Orthocord suture, the tendons are re-attached with mattress stitches by means of an arthroscopic grasper (Mitek). We use the Standard single-row technique with re-insertion at the original site. in indicated cases we carry out tenotomy or tenodesis of the long head biceps tendon. Acromionplasty follows only in type III acromion cases. After surgery the limb is immobilized in a Gilchrist bandage for 5 weeks during which, in accordance with the strength of re-attachment, passive exercise is carried out. Rehabilitation therapy should continue for 6 months at least. The results were evaluated on the basis of the UCLA (University of California at Los Angeles) shoulder rating System and the Constant scoring System. Using the school marking System (1, best; 5, worst) we asked about patients' satisfaction with surgery and their willingness to undergo the same Operation again. RESULTS Of the 77 patients treated for massive rotator cuff tears by arthroscopic repair up to 2006, 40 were fully evaluated.The average pre-operative Constant score was 48.4 (26-83) points and the UCLA score was 13.8 (6-25) points; post-operatively, these values increased up to 85.45 and 30.35 points, respectively. In addition to rotator cuff repair, we performed tenotomy or tenodesis of the long head biceps tendon (31x; in seven cases a tendon rupture was present), acromioplasty (17x), acromioclavicular Joint resection (3x), subscapular muscle reconstruction (5x) and treatment for shoulder instability (3x). In four patients we recorded the following complications: transient paresis of the upper extremity one, infection in one, and long-term secretion from the ventral portal in two patients. They were completely treated. All patients were satisfied with the treatment outcome and expressed willingness to undergo the surgery again, if needed. DISCUSION Although the arthroscopic repair of a massive rotator cuff tear is a technically demanding procedure with a long learning curve, since 2005 all rotator cuff repairs at our department have been carried out arthroscopically The results achie-ved are comparable with those of the mini-open surgery and, in addition, this method allows us to treat all co-existent pathologies at one stage. The Spiralock anchor (Mitek) proved to be an optimal implant for re-attachment of the rotator cuff tendons. No evaluation of a similar patient group is available in the relevant Czech literature, but the results are in agreement with those of published international studies. CONCLUSION Arthroscopic rotator cuff repair can be recommended as the procedure fully comparable with the open technique. Becau-se of the possibility to diagnose and treat all shoulder pathologies at one stage, all rotator cuff repairs at present carried out at our department are arthroscopic procedures.
Keywords: Minimally Invasive Surgical Procedures; ruptura; Magnetic Resonance Imaging; Rupture; poranění šlachy; Arthroscopy; Data Interpretation, Statistical; artroskopie; Rotator Cuff; miniinvazivní chirurgické výkony; radiografie; poranění rotátorové manžety; magnetická rezonanční tomografie; Tendon Injuries; interpretace statistických dat; Radiography; Rotator Cuff Injuries; rotátorová manžeta